Antecedents of Competitive Advantage and Its Consequences on Business Performance - IA Cynthia Saisaria Mandasari; I Ketut Rahyuda; Ni Wayan Ekawati; Putu Yudi Setiawan (International Journal of Social Science and Business, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are one of the popular economy sectors that play an important role in advancing Indonesia's economy. The high number of MSMEs in Indonesia certainly increases the competition among MSMEs. Thus, to survive, MSMEs need continuous improvement in their Business Performance. This study aims to analyze the antecedents of competitive advantage and their consequences for business performance moderated by live streaming commerce. The method of writing scientific articles is by using qualitative methods and literature studies or library research. Reviewing theories and reviewing literature books that are in accordance with the theories discussed. The results of this study indicate that Entrepreneurial marketing has a positive and significant effect on business performance. E-commerce adoption has a positive and significant effect on business performance. Entrepreneurial marketing has a positive and significant impact on competitive advantage. E-commerce adoption has a positive and significant effect on competitive advantage. Competitive advantage has a positive and significant effect on business performance. Live streaming commerce moderates the influence of entrepreneurial marketing on business performance. Live streaming commerce moderates the effect of e-commerce adoption on business performance. Competitive advantage mediates the effect of entrepreneurial marketing on business performance. Competitive advantage mediates the effect of e-commerce adoption on business performance.